2021
DOI: 10.6007/ijarbss/v11-i8/10792
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Speech Acts Between Malaysia and Singapore on the First MCO Announcements of Covid-19

Abstract: The purpose of the study was to analyse the use of speech acts on the first announcements of Covid-19 Movement Control Order (MCO) by the Prime Ministers of Malaysia and Singapore. It was also to discover if there were differences in the forms of these announcements which affected the nation in their respective countries. This study employed a qualitative method of analysis. The MCO announcements were taken from the available open sources. The data was analysed based on Searle's framework of speech Acts. It wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Similarly, Altikriti (2016) reported that constative speech acts were prominent in President Obama's speeches, whereby he utilized more assertive sentences as compared to the other speech acts. These studies indicated the cruciality of speech acts in leadership, especially the role of constative acts as persuasive speech acts (Krishnan et al, 2021). Consequently, the findings of this study may suggest that the participants were persuasive and compelling in their communication and leadership roles.…”
Section: Constativementioning
confidence: 55%
“…Similarly, Altikriti (2016) reported that constative speech acts were prominent in President Obama's speeches, whereby he utilized more assertive sentences as compared to the other speech acts. These studies indicated the cruciality of speech acts in leadership, especially the role of constative acts as persuasive speech acts (Krishnan et al, 2021). Consequently, the findings of this study may suggest that the participants were persuasive and compelling in their communication and leadership roles.…”
Section: Constativementioning
confidence: 55%
“…Members of another culture, according to him, are unable to attach more culture invaluableness to the generosity maxim than do others. Krishnan et al, 2021) argues that concerning the approbation maxim, the speaker must minimise the expression of beliefs that express disapproval of others, maximise the expression of beliefs, which express approval of others. He argues that because utterances are equal, people praise others, have a minimal response, or become silent.…”
Section: Leech (1983)mentioning
confidence: 99%
“…On-record super-strategies entail performing face-threatening acts using negative politeness as the speakers may decide to avoid it when its degree is huge. Therefore, if there is a lack of redress, external factors compel the addressers to speak differently during emergencies and channel limitations (Krishnan et al, 2021). The speakers may focus on the propositional content of the message and disregard the interpersonal aspect of an utterance during danger or requiring someone to act.…”
Section: Thomas (1995)mentioning
confidence: 99%
See 2 more Smart Citations